Analisis Pengaruh Model Turbulen dalam Simulasi CFD Centrifugal Fan menggunakkan Ansys - Bagas Santoso; Delima Yanti Sari; Hendri Nurdin; Fitrah Qalbina (Jurnal Vokasi Mekanika (VoMek), 2025)
The study was conducted to determine the airflow in the backward type centrifugal fan using Computational Fluid Dynamics (CFD) simulation. This type of fan is often used in various industries due to its high efficiency in moving air or gas. In CFD simulation, the selection of the right turbulent model is very important to obtain simulation results that are reliable, efficient, and relevant to real conditions. The study used four different turbulent models to look at their effects on pressure distribution, flow velocity, and fan efficiency. The turbulent models used are k-? Standard, k-? RNG, k-? Realizable and k-? SST. The goal was to find the most optimal turbulent model of the centrifugal fan around the impeller. The impeller has an angle (,?-1.) of 35,260 with a rotation speed of 301,069 rad/s. The simulation was carried out by meshing about 500,000 mesh elements for a balance between accuracy and computing needs. Validation was carried out by comparing the simulation results of Ansys Student R1 2024 and Solidwork. Of the four turbulent models tested, k-? RNG provided the most accurate results, with an efficiency difference of only 1.3% compared to Solidworks. This model manages to capture better variations in pressure and flow velocity, especially in turbulent areas and around the impeller. These results show that the k-? RNG turbulent model provides closer results than other models. These findings are important for the optimization of centrifugal fan design and emphasize the importance of selecting the right turbulent model in numerical simulations.